Desensitization in the Era of Precision Medicine: Moving From the Bench to Bedside. Issue 8 (August 2019) - Habal, Marlena V; Farr, Maryjane; Restaino, Susan; Chong, Anita
Abstract : Patients with antibodies to HLA wait longer for transplant and are at increased risk of adverse outcomes. For more than a decade, drug therapy approaches have been tested to modulate the immune system to prevent or reduce donor-specific antibody levels. Despite some studies reporting success in facilitating transplant, many patients do not respond or experience donor-specific antibody rebound, highlighting the diversity of the individual patient's immune response. While advances in immunomodulatory therapies have resulted in escalating efforts to successfully treat highly sensitized patients, further insight into the human immune system has uncovered its enormous complexity and diversity calling for a personalized approach. Yet, even defining the sensitized transplant candidate can be troublesome and much remains to be understood about the interaction between an individual's immune system as a whole and their response to our current desensitization strategies. The shift toward a personalized approach calls for a reevaluation of what we know and what remains to be determined; a process that will require iterative translational approaches. This review will focus on new insights into how the interaction between immune risk assessment, the patient's immunological history, and the clinical context can be reconciled to develop a precision-based approach to pretransplant management.